PSYCHOANALYSIS IN EDUCATION: AN IMPOSSIBLE JOB OR AN IMPROBABLE DIALOGUE - Amilton da Costa, José; Cristina Medeiros de Azevedo Silva, Ana; Dias Costa, Cleide; Araújo da Costa, Marluce; Medeiros, Salésia (Revista Gênero e Interdisciplinaridade, 2025)
This article discusses the interfaces between the fields of Education and Psychoanalysis, presenting the contributions of the latter to the pedagogical field, treating the student as a subject rather than an object. To this end, the psychoanalytic perspective applied to educational practice was observed, seeking to understand the possibilities and/or impossibilities of this articulation, focusing on themes such as sexuality, the desire to know, affectivity, and transference. At the same time, it reveals the role of educational practices in the constitution and development of the subject. Therefore, it reaffirms the need for dialogue between these specific fields, reiterating that this interrelation is possible and contributes positively to the development of both and those who utilize them.